THE TRANSFORMATIONAL LEADERSHIP ROLE OF PRINCIPALS AND JOB SATISFACTION IN IMPROVING TEACHER PERFORMANCE IN MTS TUNAS HARAPAN BANGSA NYALINDUNG KAB. SUKABUMI - Anisa dewi Raharja; Mulyawan Safwandy Nugraha (Media Inovasi Pendidikan dan Publikasi, 2023)
The purpose of this study is to describe the role of transformational leadership and teacher job satisfaction in improving teacher performance in Mts Tunas Harapan bangsa. In detail, this study was conducted to answer the following research questions: how high is teacher job satisfaction, how high is the transformational leadership role that the principal has and should implement and how high is the resulting teacher performance. The research method used is descriptive qualitative, meaning that researchers go directly into the field to see and analyze the situation after it is described in a scientific article. Data collection is carried out by observation, interviews, sources to teachers and principals, as well as documentation collected. From the results of this study that the role of transformational leadership in the school has been carried out and influential but teacher job satisfaction is still lacking so that it affects the resulting performance. Therefore, researchers are further encouraged to continue this research in the context of work motivation variables which will later produce good job satisfaction and will have a positive effect on improving good teacher performance.